2015
DOI: 10.3944/aott.2015.15.0158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pentoxifylline on the Healing of Segmental Bone Defects and Angiogenesis

Abstract: According to radiological and histological parameters, PTX appears to improve angiogenesis and healing of segmental cortical bone defects of the radius in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The VEGF levels were higher in the skin flap than in the serum of the animals, and both showed a significant increase in this protein in the treated groups. This result suggests that pentoxifylline stimulated the production/ liberation of this important angiogenic molecule and corroborate with the results in the literature 32 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The VEGF levels were higher in the skin flap than in the serum of the animals, and both showed a significant increase in this protein in the treated groups. This result suggests that pentoxifylline stimulated the production/ liberation of this important angiogenic molecule and corroborate with the results in the literature 32 .…”
Section: Discussionsupporting
confidence: 93%
“…Other 8,9,11,13,14,[16][17][18][19][28][29][30][31][32] have demonstrated that parenteral administration of pentoxifylline with different schemes and doses ranging from 1 to 50 mg/kg, was able to improve tissue vitality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, we believe that an increase in vascularization results in a relatively faster tendon repair. In the study conducted by Çakmak et al [28] on the segmental bone defects in rats, it has been shown that PTX increases vascularization and angiogenesis in the defect area by increasing cluster of differentiation-31 (CD-31) and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…PTX was originally used as a hemorheologic drug to treat intermittent claudication, with minor side effects [16]. Previous studies report positive effects of PTX alone or in combination with other drugs on some pathologic bone diseases including osteoradionecrosis, arthritis; as well as an ability to accelerate osteogensis and fracture healing in both animal models and human patients [1718192021222324252627]. However, only a few studies have elucidated the effects of PTX on osteoporotic cells in vitro or in cases of corticosteroid-induced OP.…”
mentioning
confidence: 99%